Transition towards the artificial intelligence via re-engineering of digital platforms: comparing European Member States - Alfonso Marino; Paolo Pariso; Michele Picariello (Entrepreneurship and Sustainability Issues, 2022)
t. The present study is directed at comparing the performances of the 27 European Member States in the period 2012 – 2021 with the choice of assessing their improvement in the transition toward Artificial Intelligence. The study, opening from an analysis of the key factors with strategic rate in the countries’ transition, is centered on society, law, physiology, and trust impacts. The valuation of the effects was evaluated by seeing forty - two official European Commission rapports in order to create a composite analysis and assessment of the state of the transition in Europe. The study pointed at understanding the degree of transition related to 27 European Member States in the realization of AI targets. The outcomes of the study highpoint that the transition, evaluated with the support of the composite analysis, is current with a different degree between the Member State and only some elements could be evaluated as suitable in the transition toward an artificial intelligence system in the Europe.